An introduction to R for spatial analysis & mapping - Brunsdon, Chris; Comber, Lex (New Delhi: SAGE, 2015)
"R is a powerful open-source computing tool that supports geographical analysis and mapping. For geographers and 'non-geographers' alike, this text provides an introduction to the use of R for spatial statistical analysis, geocomputation, and the analysis of geographical information. ... A core resource for anyone collecting and using spatially referenced data, this is the definitive 'how to' that takes students--from any discipline--from coding to actual applications and uses of R."--Page [4] of cover.
Data and plots -- Handling spatial data in R -- Programming in R -- Using R as a GIS -- Point pattern analysis using R -- Spatial attribute analysis with R -- Localised spatial analysis -- R and internet data.
Includes bibliographical references and index.
Keywords: R; COMPUTER PROGRAMMING- LANGUAGE; SPATIAL ANALYSIS (STATISTICS)